Evaluating Students' Experiences with Project-Based Learning in Online Educational Contexts - Singgih Subiyantoro (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2024)
In the contemporary landscape of education, integrating Project-Based Learning (PjBL) within online educational environments has emerged as a prominent pedagogical approach, aiming to foster students' critical thinking, collaboration, and problem-solving skills. This study seeks to evaluate students' experiences with Project-Based Learning in the context of online education, recognizing the significance of understanding the effectiveness and challenges associated with this instructional method. The primary aim of this research is to assess the perceptions and experiences of students engaging in Project-Based Learning within online educational settings. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews to capture students' perspectives comprehensively. The study sample comprised students enrolled in diverse online courses across various disciplines, ensuring a broad representation of experiences and insights. The study's main results reveal a nuanced understanding of students' experiences with Project-Based Learning in online educational contexts. Quantitative analysis indicates overall positive perceptions regarding the effectiveness of PjBL in enhancing learning outcomes and fostering student engagement. Qualitative findings further elucidate the multifaceted nature of students' experiences, highlighting both the benefits and challenges of implementing PjBL in online settings. In conclusion, this research underscores the potential of Project-Based Learning as a valuable instructional approach within online education, offering opportunities for meaningful learning experiences and skill development. However, it also identifies several considerations and areas for improvement, such as adequate technological support, clear guidelines, and enhanced facilitation to optimize the PjBL experience in online environments. This study contributes to the field of education by providing empirical insights into implementing Project-Based Learning in online educational contexts. The findings offer valuable implications for educators, curriculum designers, and policymakers seeking to effectively integrate innovative pedagogical approaches into online learning environments, ultimately enhancing the quality and efficacy of online education.